2006
DOI: 10.1142/s021827180600884x
|View full text |Cite
|
Sign up to set email alerts
|

Paraboloidal Space–times and Relativistic Models of Strange Stars

Abstract: The objective of this paper is to find out the suitability of an ansatz similar to that suggested by Vaidya–Tikekar, but prescribing paraboloidal geometry for the 3-space of the interior space–time of a relativistic spherical star in describing a family of physically viable models of superdense stars like Her X-1, SAX, and X-ray brust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Following Sharma et al [12] we have chosen central density ρ 0 = 4.68×10 15 g cm −3 . The behaviour of ρ and P for models obtained for different chosen values of the compactification factor are described graphically in figures 1, 2 and 3 after appropriately scaling the dynamical variables as ρ , P as in [18] using the relations ρ(z) = ρ (z) × 10 14 g cm −3 and P (z) = 7 × 10 33 · P (z) dyn cm −2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Sharma et al [12] we have chosen central density ρ 0 = 4.68×10 15 g cm −3 . The behaviour of ρ and P for models obtained for different chosen values of the compactification factor are described graphically in figures 1, 2 and 3 after appropriately scaling the dynamical variables as ρ , P as in [18] using the relations ρ(z) = ρ (z) × 10 14 g cm −3 and P (z) = 7 × 10 33 · P (z) dyn cm −2 .…”
Section: Discussionmentioning
confidence: 99%
“…Finch and Skea have shown that this two-parameter family of solution is not only regular and physically viable for a range of its parameters, but also to a good approximation suitable to describe the interiors of neutron stars in equilibrium by comparing numerical models with neutron star models based on the relativistic mean field theory of Walecka [17]. We shall see in the next section that this family of solutions is also suitable to describe the interiors of other compact stars such as strange stars, hybrid neutron stars etc [18].…”
Section: General Two-parameter Family Of Solutionsmentioning
confidence: 99%
“…Due to cumbersome expressions of (25), (27) and (30), the trend of pressure-density ratio and adiabatic sound speed will be studied numerically after applying the boundary conditions.…”
Section: Properties Of the New Solutionmentioning
confidence: 99%
“…This approach leads to physically viable and easily tractable models of superdense stars in equilibrium. Tikekar and Jotania [87,88], Jotania and Tikekar [89] showed that the ansatz suggested by Tikekar and Thomas [90] has these features and the general three-parameter solution based on it also leads to physically plausible relativistic models of strange stars. Several aspects of physical relevance and the maximum mass of class of compact star models, based on Vaidya-Tikekar ansatz, for the both isotropic and anisotropic pressures have been investigated in [53,[91][92][93].…”
Section: Introductionmentioning
confidence: 98%